Let's party! Things to make and do! - Parragon (United Kingdom: Parragon, 2011)
The book "Disney Pixar Cars: Let's Party! Things to Make and Do" is a fun and creative activity guide for kids. It features easy, step-by-step instructions to help children make exciting party crafts and decorations inspired by the popular Cars movie characters. From race cars to party hats and fun games, the book encourages kids to use their imagination and enjoy hands-on activities. With colorful pictures and simple directions, it's perfect for planning a themed party or just having fun at home. This book makes learning and crafting both easy and entertaining for young readers.
location: 2C
Keywords: Art and craft book